Implementasi Kriptografi Pengamanan Data Soal Ujian di Lingkungan Perguruan Tinggi Menggunakan Algoritma AES-256 dan SHA-256 - Iwan Setiadi; Santi Widianti; I Putu Prachanda Kayuan (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses the implementation of cryptographic technology for securing exam questions in a college environment, focusing on the use of the AES-256 and SHA-256 algorithms. The purpose of this study is to protect exam questions from the threat of leaks and ensure the authenticity of the questions received by students. In the experimental method in the proposed scientific writing, exam questions will be encrypted using the AES-256 algorithm, while the SHA-256 algorithm is used to generate a unique hash value that maintains the integrity of the question data, where the hash itself is an alphanumeric code generated from the process of converting digital data through certain mathematical functions. The AES-256 and SHA-256 Cryptographic Algorithms are chosen as algorithms to secure exam questions, Oracle VM VirtualBox and Kali Linux as the types of software/operating systems chosen to run the AES-256 and SHA-256 cryptographic algorithms. expected with strong protection against the threat of data leaks and manipulation, and ensure that the exam questions received by students remain original and do not change and are maintained authenticity.